Job Design as a Predictor of Employee Engagement in Managing Disruptions in the Public Health Sector in Kenya - Muchibi, Wilbrodah Mutsoli (Human Resource and Leadership Journal, 2025)
Purpose: This research paper aimed to study Job Design as a Predictor of Employee Engagement in Managing Disruptions in the Public Health Sector in Kenya's Western Region. Methodology: The study adopted a descriptive research design and the theoretical framework drew from Job characteristics model. The study targeted a population of 3,092 from which a sample size of 342 respondents was drawn using stratified and simple random sampling techniques. A proportionate allocation was used to select a representative sample from each stratum and a self-administered questionnaire used to collect the required data with a reliability of 0.737. Quantitative data was analysed using frequencies, percentages, means, standard deviations (descriptive) and correlation and basic linear regressions based the inferential statistics. Thematic content analysis was used to analyse qualitative data. The relationship among the variables was tested using a t-test at 5% significance and an F test. Findings: The study found out that job design (r=0.721p<0.000, R2=0.519) had a strong significant influence on employee engagement. Therefore, provision of work autonomy, task identity and task variety to nurses and doctors would enhance their engagement. Further, specifying the way of performing the tasks by establishing employees’ responsibilities, roles, procedures, and the systems that should be used boost their engagement which will go a long way in managing disruptions on provision of primary healthcare services brought about by occasioned threats for and holding demonstrations and strike actions. Unique Contribution to Theory, Policy and Practice: The study’s theoretical framework contributes to the knowledge of research by the Public Health Sector Administrators using the three job characteristics; task identity, work autonomy and task variety activities as a checklist for job analysis or job development. Similarly, they may come up with motivational strategies such as job rotation, job enrichment, varying assigned work, combining tasks, delegating tasks, team work and encouraging sharing of ideas. This increases the happiness of workers, teaches new talents, which adds engaging elements to the position. Accordingly, the mixed methodology of data collection, analysis, and procedures contributes to the field of human resource management by investigating the influence of job design on employee engagement. Therefore, this study provides a better reference point for administrators on how to link job design to employee engagement in the public health sector in Kenya.